Institutional resilience and AI adoption in a turbulent economic context: perceptions across stakeholders - Toro-Dupouy, Luis; Erdmann, Anett (Transformations In Business & Economics, 2026)
Why should institutions care about stakeholders’ perceived institutional resilience when shaping AI deployment strategies? This study investigates how institutional resilience influences AI adoption intention in higher education, addressing the gap between capability-based management and stakeholder behavior intention. Using PLS-SEM and Necessary Condition Analysis in a multi-group study, we analyze faculty and students across program types. Results show that the effect of perceived institutional resilience on AI adoption intention is fully mediated by stakeholders’ perceived value of AI. This mechanism is robust across groups and program delivery modes. However, while perceived AI value acts as a driver of adoption for both stakeholder groups, behavioral conditions differ: students require a minimum perceived AI value for high adoption intention, while faculty respond to perceived value in a more gradual, stepwise manner to achieve high levels of adoption. This underscores the need for value-based AI deployment strategies that account for institutional context and stakeholder constraints.